Scale-up considerations for a hollow-fiber-membrane bioreactor treating trichloroethylene-contaminated water - Pressman, Jonathan G (Water environment research : a research publication of the Water Environment Federation, 2005)
Scale-up of a hollow-fiber-membrane (HFM) bioreactor treating trichloroethylene- (TCE-) contaminated water via co-metabolism with the methanotroph Methylosinus trichosporium OB3b PP358 was investigated through cost comparisons, bioreactor experiments, and mathematical modeling. Cost comparisons, based on a hypothetical treatment scenario of 568-L/min (150-gpm) flowrate with an influent TCE concentration of 100 microg/L, resulted in a configuration of treatment trains with two HFM modules in series and an overall annual cost of US dollar 0.36/m3 treated. Biological experiments were conducted with short lumen and shell residence times, 0.16 and 0.40 min, respectively, as a result of the cost comparisons. A new variable, specific transformation, was defined for characterizing the cometabolic transformation in continuous-flow systems, and values as large as 38.5 microg TCE/mg total suspended solids were sustainable for TCE treatment. Using mathematical modeling, HFM bioreactor system design was investigated, resulting in a five-step system design strategy to facilitate sizing of the unit processes